2020
DOI: 10.1080/23294515.2020.1737982
|View full text |Cite
|
Sign up to set email alerts
|

Informed Consent in Two Alzheimer’s Disease Research Centers: Insights From Research Coordinators

Abstract: Background: Informed consent (IC) is critical to performing ethical research. Unfortunately, the IC process and supporting IC forms are frequently burdensome and do not necessarily meet the informational needs of participants. The intersecting legal and ethical challenges of obtaining IC from individuals with memory or cognitive deficits further exacerbate existing IC shortcomings. For this reason, study coordinators play a critical role in facilitating the IC process in Alzheimer's disease (AD) research. To i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Interviews with study coordinators from the two ADRC teams about their paper-based IC process identified key challenges: difficulties maintaining participant attention, explaining complex procedures, and modifying the IC process to support the needs of individual participants [19]. Often, such challenges are not specifically considered as part of IRB review.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interviews with study coordinators from the two ADRC teams about their paper-based IC process identified key challenges: difficulties maintaining participant attention, explaining complex procedures, and modifying the IC process to support the needs of individual participants [19]. Often, such challenges are not specifically considered as part of IRB review.…”
Section: Discussionmentioning
confidence: 99%
“…We produced a participant-centric, interactive eIC experience that incorporates IC best practices such as using simplified language, graphics, comprehension questions with corrective feedback [16][17][18], and tiered information (i.e., allowing participants to access supplemental information about specific concepts). This eIC approach addressed some of the barriers to an effective IC process that ADRC study coordinators previously identified, including making it easier to customize the order in which information is presented to research participants [19]. The eIC experience was piloted with study coordinators and participants who provided input on which features of eIC were most relevant and meaningful to them (manuscript in preparation).…”
Section: Introductionmentioning
confidence: 99%
“… 7 CRCs perform tasks, such as screening study subjects, patient education and acquisition of informed consent, scheduling clinical visits and contacting study subjects, completing case report forms, observing adverse events, and liaising with researchers and sponsors. 9 , 10 , 11 As CRC nurses work on the front lines from the beginning to the end of clinical trials, 12 they can best identify the main reasons for participation and withdrawal from clinical trials and suggest potential remedial measures. Many studies have assessed motivations for or barriers to clinical trial participation as well as the reasons for study withdrawal by surveying the participants or physicians.…”
Section: Introductionmentioning
confidence: 99%